STRATEGI IMPLEMENTASI TQM DALAM MENINGKATKAN KINERJA OPERASIONAL DAN KEPUASAN PELANGGAN PADA MCDONALD’S - PUTRI, LIVIANA NADILA AZAHRA; HUDA, MIFTAKUL; SUCIPTO, FIANTO ADY; RAHMAN, RIFKI; AMBARANI, EKA DWI (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study looks at how McDonald's can use Total Quality Management (TQM) as a strategy to improve operational performance and customer satisfaction. TQM is used to ensure product and service quality at every stage of operations, including regular quality audits and employee training. This study used quantitative methods. 101 respondents received questionnaires to assess their perceptions of various aspects of the service. Results show that total quality management (TQM) improves customer satisfaction and operational efficiency, but some aspects need improvement, such as off-peak order handling and order accuracy. McDonald's has demonstrated the ability to maintain high global quality standards and increase its competitiveness in the fastfood restaurant industry by implementing a total quality management (TQM) system).